Valzhyna Mort, Music for the Dead and Resurrected (Altre Modernità, 2021)
Valzhyna Mort, Music for the Dead and Resurrected (New York, Farrar Straus & Giroux, 2020, 95 pp.  ISBN 978-037-425-206-9)di Rossella Carìa